Stress induced carbon fiber orientation for enhanced thermal conductivity of epoxy composites. (1st March 2021) - Li, Maohua; Ali, Zulfiqar; Wei, Xianzhe; Li, Linhong; Song, Guichen; Hou, Xiao; Do, Hainam; Greer, James C.; Pan, Zhongbin; Lin, Cheng-Te; Jiang, Nan; Yu, Jinhong
Abstract: Polymer composites that have high thermal conductivity have become one of the most promising solutions needed to satisfy the thermal management requirements for high-power electrical and electronic equipment. In this work, a strategy relying on aligning carbon fibers through the application of a stress field is proposed. Ultrahigh through-plane thermal conductive epoxy composites with carbon fiber networks have been prepared by in-situ solidification within an epoxy. The thermal conductivity of these epoxy composites reaches as high as 32.6 W m −1  K −1 at 46 wt percent (wt%) of carbon fibers, which is about 171 times that of the pure epoxy. The alignment condition for the carbon fibers for a carbon fiber composite in which stress has been applied and a blended carbon fiber composite are compared using micro compute tomography (micro-CT) and scanning electron microscopy (SEM). These epoxy composites display attractive thermal properties and provide a practical route to satisfy the thermal dissipation requirements raised by the development of modern electrical devices and systems. Graphical abstract: Image 1 Highlights: Aligning carbon fiber to preparing high through-plane thermal conductive composite. Using mechanical method to construct thermal conductive path. Thermal conductivity rises with well-alignment of filler becomes. This method is simple and its cost is low.